Pengaruh layanan bimbingan kelompok teknik symbolic modelling terhadap peningkatan rasa percaya diri siswa slow learner - Muhammad Yasril Yusuf; Enik Nurkholidah; Drajat Edy Kurniawan; Fauziah Fauziah (Journal of Counseling, Education and Society, 2025)
This study aimed to examine the effectiveness of the symbolic modeling method in enhancing students’ self-confidence. A quantitative approach with a pre-experimental design, specifically a one-group pre-test and post-test design, was employed. The participants were seven eighth-grade students of SMP Negeri 2 Sewon in the 2023/2024 academic year, selected through purposive sampling based on low self-confidence levels, willingness to participate, and consistent attendance. Data were collected through interviews, observations, documentation, and the Student Self-Confidence Instrument (IKD), which was developed based on seven indicators: willingness and effort, optimistic attitude, independence, self-worth, adaptability, ability to utilize strengths, and positive thinking. The instrument, constructed in the form of a Likert scale, demonstrated validity through expert judgment and reliability with a Cronbach’s Alpha above 0.70. The intervention consisted of three sessions of symbolic modeling, focusing on modeling confident behavior through symbolic stories, role models, and reflective activities. Data analysis employed descriptive statistics and a paired sample t-test. Results indicated an increase in the mean self-confidence score from 58.43 (pre-test) to 83.71 (post-test), reflecting an improvement of 25.28 points. The paired sample t-test showed a significant difference (t = 8.521; p < 0.05), confirming the effectiveness of the intervention. Thus, symbolic modeling was found to effectively enhance self-confidence among students, particularly those with learning difficulties. However, limitations include the small sample size, lack of a control group, and short intervention period. Future studies with larger samples, more rigorous designs, and extended interventions are recommended to strengthen and generalize the findings.